2017
DOI: 10.1002/met.1691
|View full text |Cite
|
Sign up to set email alerts
|

Verification and bias correction of ECMWF forecasts for Irish weather stations to evaluate their potential usefulness in grass growth modelling

Abstract: Typical weather in Ireland provides conditions favourable for sustaining grass growth throughout most of the year. This affords grass based farming a significant economic advantage due to the low input costs associated with grass production. To optimize the productivity of grass based systems, farmers must manage the resource over short time scales. While research has been conducted into developing predictive grass growth models for Ireland to support on-farm decision making, short term weather forecasts have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Studies from around the world have reported this problem: McDonnell et al . (2018) and Ghosh et al . (2018) reported inconsistent P ECMWF results for Ireland and southern Asia, respectively.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Studies from around the world have reported this problem: McDonnell et al . (2018) and Ghosh et al . (2018) reported inconsistent P ECMWF results for Ireland and southern Asia, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…McDonnell et al . (2018) found ECMWF errors <10% between P data from meteorological ground stations and ECMWF data in Ireland and ensured that ECMWF data could be used to estimate grass biomass.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Further details on these bias correction techniques are available in McDonnell et al (2018) and Joliffe and Stephenson (2011).…”
Section: Weather Forecasts and Observationsmentioning
confidence: 99%
“…The inclusion of forecasts will introduce an extra level of uncertainty to the model. McDonnell et al (2018) assessed the accuracy of European Centre for Medium-Range Weather Forecasts (ECMWF) forecasts at 25 Irish weather stations, and applied bias correction techniques to improve forecast accuracy. Air temperatures were forecast accurately up to ten days in advance, with improvements after bias correction, and rainfall forecasts generally performed well up to five days in advance.…”
Section: Introductionmentioning
confidence: 99%